PTU-178 Measurement of esophago-gastric junction cross-sectional area and distensibility by EndoFLIP® (endolumenal functional lumen imaging probe) for the diagnosis of patients with gastro-esophageal reflux disease (GERD). (28th May 2012) - Tucker, E; Sweis, R; Anggiansah, A; Telakis, E; Wright, J; Knowles, K; Wong, T; Fox, M
Abstract : Introduction: EndoFLIP ® (Crospon, Ireland) is an innovative device designed to assess the cross sectional area (CSA) and distensiblilty of the esophagogastric junction (EGJ) by combined impedance planimetry and pressure measurement. Initial studies have suggested that this probe may distinguish between gastro-oesophageal reflux disease (GERD) patients and healthy volunteers (HV). Aim: To assess the diagnostic agreement of EndoFLIP ® measurements with clinical and physiologic GERD diagnosis. Methods: 22 healthy volunteers, (HV; female=16, age 21–46, mean body mass index (BMI) 24.3 kg/m 2 ) and 20 patients with GERD symptoms (female=14, age 19–78, mean BMI 33.2 kg/m 2 ) were studied. Patients were older (p<0.0001) and had greater BMI (p=0.001). Median EGJ CSA and distensibility at 20 ml and 30 ml EndoFLIP ® balloon volume were measured. A Bravo capsule (Given Imaging, Israel) was attached 6 cm above the Z-line and a 48 h wireless esophageal pH recording acquired. The ability of EndoFLIP ® measurements to discriminate (1) patient group and (2) individuals with pathologic acid exposure (>5.6% time <pH4) was calculated. Results: Complete measurements were acquired except in one patient with early detachment of Bravo capsule. Distensibility could not be measured in one patient and one volunteer with negative endoFLIP® balloon pressures. 7/22 (32%) HVs and 7/19 (37%) of patients had oesophagitis (six patients with hiatus hernia). 3/22 (14%) HVs and 9/19 (47%) patients had pathologic acid exposure (p=0.126). EGJ CSA was higher in healthy volunteers than the patient group, at 20 ml (p=0.018) and 30 ml (p=0.058, Abstract PTU-178 figure 1 ) endoFLIP® balloon volume. EGJ distensibility was lower in patients than HVs at 20 ml (p=0.001) and 30 ml balloon volume, (p=0.020, Abstract PTU-178 figure 1 ). EndoFLIP® measurements were similar in participants with and without pathologic acid exposure (median CSA 40 mm 2 vs 34 mm 2 p=1.0 at 20 ml, 98 mm 2 vs 107 mm 2, p=0.789 at 30 ml) and distensibility at 20 ml (p=0.574) and 30 ml balloon volume (p=0.704). Post-hoc analysis revealed an inverse association between BMI and CSA (R 2 =0.214, p=0.003) and negative association with distensibility (R 2 =0.211, p=0.003). BMI was associated also with a trend to increased acid exposure (p=0.116). Conclusion: EndoFLIP® is not useful for GERD diagnosis as EGJ CSA and distensibilty do not distinguish between HVs and GERD patients defined by clinical presentation or pH measurement. This unexpected result may be due to an important interaction of obesity with EndoFLIP® measurements. Competing interests: None declared.